دیاریی دیمۆگرافی (پەنجەرەی دیمۆگرافی) و بژاردەكانی لە بەردەم هەرێمی كوردستاندا - تالیب, پ.د.جەزا تۆفیق; حمە, د.سروە جلال (Sulaimani Journal for Humanities, 2023)
The current research paper which is titled (The Demographic Donation (The Demographic Window ( and Its Options Before Kurdistan Region), aims at showing the trends of demographic changes and the changes at the age structure of the population of Kurdistan Region in result of moving on of the population numbers of the age group (below 15 years) into the group of the people that fall within the age of work (economically), coupled wih a simple rise of the group of the elderly people.This refers to the fact that Kurdistan Region will soon be in the next few upcoming years nearby the scope of the demographic donation, because the age structure of the population in Kurdistan Region is young, as in (2018) the rate of the small age group (less than 15 years) amounted to (%35.8), where as the middle age group (15-64 years) was (%60.2), while the rate of the elderly (65 years onwards) was (%4). The dependency ratio of population at the research area in (1977) was (106), then in (2018) it lessend to (65), this lessening was a helpful factor for the rise of money saving and evolution of internal investment, and the employment in a way that leads to the reduction of unemployment average and rising of development level, but these matters are connected with the institutions,markets and directing the savings to useful investment. Kurdistan Region had witnessed the occurance of demographic gift through the reduction of the annual growth ratio of population as it reached to (%1.9) in (1957-1965), whereas in (2009-2018) the annual growth ratio of population of Kurdistan Region amounted to (%2.6), and it is expected to further reduce to (%1.8) in the years (2020-2040). The relation between population and development refers to the above-mentioned ratio as a motive for the increase of population development through the rise of economic and social growth ratio. This happenes only when it gets equal to the qualitative change in the population structure leads to the rise of the middle age group people who are coupable of work economically. In population pyramid the young- age group (15-29 years) pops out and the growth average of the middle- age group is high, whereas the growth average of the dependent group is low and this situation is know as the demographic donation (window). It can not happen the positive impact of the demographic donation in the development did not follow the policy of institutional integration achieved between the supply side, which represent the opening up of demographic donation and btween the demand side, which represent the active of markets and human capacity building and expanding the participation of young people in work and the elimination of fancial corruption. It seems that Kurdistan Region is moving in the oppsite direction.